The Effectiveness of Local Wisdom-Based Instructional Model in Enhancing Students’ Moral Self-Efficacy: A Case Study of Talang Mamak Values (Current Research in Education: Conference Series Journal, 2024)
This study aimed to develop, implement, and evaluate the effectiveness of an instructional model integrating the local wisdom of Talang Mamak to enhance the moral and ethical self-efficacy of high school students. Mtilizing a rigorous sequential explanatory mixed-methods design, the research initiated with a quantitative quasi-experimental one-group pre-test/post-test approach (N=30), followed by a qualitative phase involving thematic analysis of in-depth interviews with students, teachers, and key Talang Mamak figures. The model implementation demonstrated a statistically significant increase in students’ Moral Self-Efficacy scores, evidenced by the t-test results improving from a Pre-Test mean of 61.81 to a Post-Test mean of 85.70 (p = 0.000; Cohen's d of 1.95), indicating a large effect size. This high effectiveness affirms the necessity of contextual teaching and learning in character formation. However, inconsistencies in the value of honesty among subjects necessitate a critical theoretical expansion. The findings propose a reformulation of the highest moral stage to include a communal-transcendental ethical Stage to better reflect the collective, spiritual dimensions of indigenous Indonesian ethics. The Talang Mamak PjBL model is a validated, high-impact blueprint for character education. It offers a significant empirical and theoretical contribution by providing a contextually grounded and statistically confirmed and thereby strengthening national character through cultural preservation.